The Depiction of a Garland in Renaissance Religious Painting - Zvezdina, Yulia N. (Actual Problems of Theory and History of Art, 2016)
Many works of Renaissance masters demonstrate close attention to the peculiarities of decor interpretation. Often such compositions depict a garland. The article is dedicated to a number of interpretation features of this insufficiently known detail in religious painting. The magnificent examples of such compositional decisions are typical for the works of Andrea Mantegna (for example, Saint Georges, Galleria dell’Accademia, Venice, Atarpiece from the basilica of San Zeno, Verona, and Madonna of the Victory, Louvre, Paris). Garlands often express masters’ particular passion for the symbolism of fruits. Among those are the compositions of Carlo Crivelli where the glorification of Madonna and Christ is expressed in the language of traditional Christian symbols represented as fruit garlands. There is a remarkable interpretation of a garland in the works of Cosme Tura. In Madonna with the sleeping child (Galleria dell’Accademia, Venice) conventional design of zodiacal constellations in form of golden glow is combined with two realistically painted bunches of grapes and goldfinch, a traditional symbol of Christ’s sufferings. The study of a Renaissance garland shows that decorative at the first glance, this detail preserves the ancient function of glorification of a figure overshadowed by it.